2015
DOI: 10.1021/acs.langmuir.5b03809
|View full text |Cite
|
Sign up to set email alerts
|

Unique Phase Behaviors in the Gemini Surfactant/EAN Binary System: The Role of the Hydroxyl Group

Abstract: The hydroxyl group in the spacer of a cationic Gemini surfactant (12-3OH-12) caused dramatic changes of the phase behaviors in a protic ionic liquid (EAN). Here, the effects of the hydroxyl group on micellization and lyotropic liquid crystal formation were investigated through the surface tension, small-angle X-ray scattering, polarized optical microscopy, and rheological measurements. With the hydroxyl group in the spacer, the critical micellization concentration of 12-3OH-12 was found to be lower than that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…A broad interaction peak appeared at medium q , and I ( q ) decreased with the oscillation at high q . These characteristics indicated the formation of micelles . On the other hand, the I ( q ) curve of LP was rather weak, indicating no sign of micelles.…”
Section: Results and Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…A broad interaction peak appeared at medium q , and I ( q ) decreased with the oscillation at high q . These characteristics indicated the formation of micelles . On the other hand, the I ( q ) curve of LP was rather weak, indicating no sign of micelles.…”
Section: Results and Discussionmentioning
confidence: 94%
“…The sample at C 12‑2‑12 = 20% was taken as an example for further characterizations. 1 H NMR was employed to determine the composition of the two phases, with the results shown in Figure S2 . It was found that the amount of 12-2-12 in UP was around 41% of the total UP weight whereas there was little in LP.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The standard Gibbs free energy change and enthalpy and entropy changes (Δ G m 0 , Δ H m 0 , and Δ S m 0 ) for the aggregation process have been determined by the following equations: ,, Here, x cmc is the cmc expressed in mole fraction. The n = 1, because the high ion environment in PILs completely neutralizes the charge of the surfactant head groups. ,,, …”
Section: Resultsmentioning
confidence: 99%
“…The n = 1, because the high ion environment in PILs completely neutralizes the charge of the surfactant head groups. 6,25,38,39 The as-obtained thermodynamic parameters for the aggregation process are given in Tables 7−9. As can be seen from these tables, all the ΔG m 0 values were negative, suggesting that the aggregation of the surfactants in PILs was a favorable process.…”
Section: Journal Of Chemical and Engineering Datamentioning
confidence: 99%
“…The tendency of the hydrophobic tails aggregating in aqueous solution is the driving force for spherical micelles formation, which is spontaneously the primary self‐assembly behavior of surfactant. While the hydroxyls on the hydrophilic head groups display the active functional groups for hydrogen bonds formation and for secondary self‐assembly ,. According to Figure , the self‐assembly of C 12 ‐Ar‐C 12 leads to the formation of threadlike micelles, which is structurally similar to cylindrical micelles, in which the hydrophobic tails pack in the core of the micelles while the hydrophilic moieties displayed on the surface.…”
Section: Resultsmentioning
confidence: 99%